2005
DOI: 10.1002/ijc.21234
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of DNA damage in epidemic dropsy patients to carcinogenic potential of argemone oil and isolated sanguinarine alkaloid in mice

Abstract: In recent times, a higher incidence of gall bladder carcinoma in the Indo‐Gangetic basin has been linked with the consumption of contaminated mustard oil. Consumption of mustard oil contaminated with argemone oil (AO) is well known to cause clinical manifestation referred to as “epidemic dropsy.” Because sanguinarine, an active alkaloid of AO, has been shown to intercalate DNA, a possible correlation of DNA damage in epidemic dropsy patients to tumorigenic potential of AO and isolated sanguinarine alkaloid in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…It is a matter of fact, however, that sanguinarine has been listed as responsible for the toxicity of Argemone mexicana seed oil [100][101][102] . Das et al [103] reported that topical use of argemone oil (0.15-0.3 mL) or sanguinarine (4.5-18 μmol/L) followed by application of TPA induces tumor development in a murine experimental model. Ansari et al [104] also reported that intraperitoneal administration of sanguinarine induces DNA damage in Swiss albino mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a matter of fact, however, that sanguinarine has been listed as responsible for the toxicity of Argemone mexicana seed oil [100][101][102] . Das et al [103] reported that topical use of argemone oil (0.15-0.3 mL) or sanguinarine (4.5-18 μmol/L) followed by application of TPA induces tumor development in a murine experimental model. Ansari et al [104] also reported that intraperitoneal administration of sanguinarine induces DNA damage in Swiss albino mice.…”
Section: Resultsmentioning
confidence: 99%
“…Sanguinarine in argemone oil, is suspected to cause glaucoma [101,102] . Argemone oil increases incidence of bladder cancer in animal models [103] and of gall bladder cancer in humans [104] . Furthermore, sanguinarine extract from bloodroot (Sanguinaria canadensis), previously used in oral hygiene products, was discontinued until a link between product administration and occurrence of leukoplakia was established [105,106] .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, IQAs forms in vitro DNA adducts via modification of the C(11) = C(12) bond detectable by 32 P-postlabelling [186]. Although IQAs mediated DNA damage in vitro and in vivo has been published [187].…”
Section: Molecular Targets Of Secondary Metabolitesmentioning
confidence: 99%
“…This observation is the basis for the conclusion 5 that the neutral form (pseudobase) of SA and CHE can interact with proteins, it is involved in the interactions with cellular biomacromolecules and may elicit a cytotoxic response 6 . SA and CHE forms in vitro DNA adducts via modification of the C (11) =C (12) bond (calf thymus DNA, rat hepatic microsomes, NADPH, pH 7.4) detectable by 32 P-postlabelling 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The role of QBA in the genesis of epidemic dropsy syndrome (A. mexicana poisoning) has not been explicated to date 10 , although SAmediated DNA damage in vitro 11 ( Fig. 1) and in vivo [12][13][14] has been published. In studies focused on SA-mediated DNA damage in mice, the minimum genotoxically ef-…”
Section: Introductionmentioning
confidence: 99%